2018
DOI: 10.1002/pc.24828
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of thermoplastic and nanoclay on the performance properties and morphology of epoxy resin

Abstract: The present work investigates the properties and morphology of nanobent/poly(methyl methacrylate) (PMMA)/epoxy resin hybrid nanocomposites which were successfully prepared by solvent and ultrasonication methods. Nanobent ZS1 were added in amount of 1, 2, 3, and 4 wt% and 5, 10, and 15 wt% for PMMA. The fracture toughness (impact strength and critical stress intensity factor) and flexural properties were evaluated for epoxy composites. Obtained results showed improvement of the epoxy resin mechanical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…However, to reach a satisfying level of toughness, it is inevitable to use a relatively high dosage of such rigid IMPs in epoxy formulation. This obligation causes dramatic increase in viscosity and subsequently inroads serious di culties in the processability of the obtained composite [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, to reach a satisfying level of toughness, it is inevitable to use a relatively high dosage of such rigid IMPs in epoxy formulation. This obligation causes dramatic increase in viscosity and subsequently inroads serious di culties in the processability of the obtained composite [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to toughen the epoxy resin. [4][5][6] Adding the second component can effectively improve the toughness of epoxy resin, such as nano-inorganic particles, [7][8][9][10][11] rubber elastomers, [12][13][14][15][16] and thermoplastic polymers. [17][18][19][20][21] It needs to solve the agglomeration of nanoparticles in the matrix and the interfacial compatibility with the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have found that the nano‐ or micro‐fillers can be used as the third component to improve the phase morphology and properties of the binary polymer blends . The enhancement of thermal and mechanical performance can be achieved with a suitable combination of the filler and TP polymer, which also allows the TP content to be reduced.…”
Section: Introductionmentioning
confidence: 99%